2020
DOI: 10.1126/sciadv.aax2138
|View full text |Cite
|
Sign up to set email alerts
|

Scaling, rotation, and channeling behavior of helical and skyrmion spin textures in thin films of Te-doped Cu 2 OSeO 3

Abstract: Topologically nontrivial spin textures such as vortices, skyrmions, and monopoles are promising candidates as information carriers for future quantum information science. Their controlled manipulation including creation and annihilation remains an important challenge toward practical applications and further exploration of their emergent phenomena. Here, we report controlled evolution of the helical and skyrmion phases in thin films of multiferroic Te-doped Cu 2 OSeO 3 as a function of material thickness, dopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…For example, insitu Lorentz microscopy of Fe 0.5 Co 0.5 Si film showed that magnetic field can effectively deform, rotate and enlarge the helimagnetic domains by applying H along different directions [10]. Similar observation was recently reported in Te-doped Cu 2 OSeO 3 [11]. Here, in the helimagnet CrAs, we observe an anomalous shrinkage of helimagnetic domains with decreasing temperature and find the decrease of DMI in CrAs on cooling as its main driving force.…”
supporting
confidence: 86%
“…For example, insitu Lorentz microscopy of Fe 0.5 Co 0.5 Si film showed that magnetic field can effectively deform, rotate and enlarge the helimagnetic domains by applying H along different directions [10]. Similar observation was recently reported in Te-doped Cu 2 OSeO 3 [11]. Here, in the helimagnet CrAs, we observe an anomalous shrinkage of helimagnetic domains with decreasing temperature and find the decrease of DMI in CrAs on cooling as its main driving force.…”
supporting
confidence: 86%
“…This multi-Q helical state might be a result of significant contribution of anisotropic demagnetization (stray) field at the low temperatures present in the NPL, which easily transforms to a stable single-Q helical state by increasing H || by ≈100 Oe above zero field (Figure S8e-h, Supporting Information). [42,43] In principle, the transformation of topologically protected SkS to the helical phase is facilitated by the dynamics of Bloch points in the material. In earlier studies, [15,44,45] the transformation of SkS to the helical phase proceeds with the merging of SkS to the formation of Bloch points that travel across the material.…”
Section: (5 Of 8)mentioning
confidence: 99%
“…Indeed, additional magnetic phases stabilized by magnetocrystalline anisotropies -the (metastable) canted conical state as well as the low temperature skyrmion lattice phase -were found in Cu 2 OSeO 3 at low temperatures but for H only aligned along crystallographic 100 directions [18][19][20]. Recently, real space observations addressing these states have been reported for a thin Cu 2 OSeO 3 lamella and field along a 100 direction [21].…”
Section: Introductionmentioning
confidence: 99%